STRATEGI PEMBANGUNAN PABRIK PUPUK ORGANIK DI KABUPATEN JEMBER : APAKAH HANYA UTOPIA? - Amam Amam; Nur Widodo; Himmatul Khasanah; Desy Cahya Widianungrum; Basuki Basuki; Nanin Meyfa Utami (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Organic fertilizer is one of the vital elements in the cycle of sustainable agricultural development, therefore the purpose of this research is to formulate a strategy for building an organic fertilizer factory based on manure of beef cattle in Jember District. The research location is Tempurejo Sub District which is one of the locations for the building an organic fertilizer factory in Jember District. The research was conducted by quantitative descriptive method. Data was collected  using desk research, observation, Focus Group Discussion (FGD), and surveys using questionnaires. This study involved 32 key respondents in the effort to build an organic fertilizer factory in Jember District. The research data was analyzed using IFAS, EFAS, and SWOT analysis approaches. The results showed that the strength factor has a weight of 0.512 and the weakness factor has a weight of 0.488, while the opportunity factor is 0.485 and the threat factor has a weight of 0.515. The conclusion of the research was that the building an organic fertilizer factory in Jember District was carried out with an SO (strength and opportunity) strategy, which means supporting an aggressive growth policy (growth oriented strategy).